Towards a tailored lymphadenectomy for gastric cancer based on the correlation between the primary tumor location and the first lymphatic drain basin: Preliminary data. - Griniatsos, John; Moris, Demetrios; Spartalis, Eleftherios; Gakiopoulou, Hara; Karavokyros, Ioannis; Apostolou, Konstantinos; Dimitriou, Nikoletta; Felekouras, Evangelos (J BUON, 2017)
PURPOSE: The contradictory long-term results following D2 lymphadenectomy have revealed the necessity for a more tailored lymphadenectomy in cases of gastric cancer. Among the patients who had undergone a modified D2 lymphadenectomy for gastric cancer, we further analyzed the subgroup in which histologically and immunohistochemically solitary lymph node metastases were detected. Classifying the primary tumors as towards to the lesser and towards to the grater curvature, we propose possible routes of lymphatic spread and possible clinical implications. METHOD: Between January 2007 and December 2016, 212 patients suffering from gastric adenocarcinoma underwent a modified D2 lymphadenectomy. Solitary lymph node metastases were detected by histology in 14 patients (7 skip metastases) and by immunohistochemistry in an additional 10 patients (5 skip micrometastases). RESULTS: The incidence of the histologically detected solitary lymph node metastases was 6.6% for the whole cohort, increasing to 11.3% with the use of immunohistochemistry. The incidence of the histologically detected skip solitary lymph node metastases was 3.3% for the whole cohort, increasing to 5.7% with the use of immunohistochemistry. Tumors of the lower and middle third of the stomach were equally drained both to the level I and II lymph node stations. However, tumors towards the lesser curvature were mainly drained in the level II lymph node stations (12 out of 19; 63%), while tumors towards the greater curvature were all drained in the level I lymph node stations (5 out of 5; 100%). CONCLUSION: Primary gastric tumors towards the lesser curvature should be treated by a modified D2 lymphadenctomy. However, for tumors towards the greater curvature, a D1(+) lymphadenectomy always including the no. 7 & 9 lymph node stations complex, might be enough.